Challenges of teachers in implementing PATH-Fit as the new tertiary physical education in the Philippines - Ruben L. Tagare, Jr.; Norita E. Manly; Joseph Lobo; Ronel Peromingan; Mary Ann Salazar; Irish M. Orgeta; Yashier T. Haji Kasan; Armand G. Aton; Sarah Jane B. Labarda; Mark Anthony R. Dalipe; Jay Mark D. Sinag; Mark Anthony B. Rosario; Jomar B. Esto (Journal of Education and Learning (EduLearn), 2026)
This research aimed to comprehensively investigate the challenges faced by physical education teachers in implementing physical activities towards health and fitness (PATH-Fit) as the new tertiary physical education curriculum in the Philippines. Employing a qualitative research design, the study engaged five physical education teachers from a leading State University in the Southern Philippines as the main source of data. The research participants were actively involved in focus group discussions and in-depth interviews using an open-ended guide questionnaire validated by experts in the field. The triangulation of results revealed five essential themes capturing the significant challenges faced by these educators in the implementation of the new curriculum: inadequate instructional references, insufficient instructional time for PATH-Fit, lack of training and retooling for teachers, unavailability of equipment and materials, and shortfall on administrative support and guidance. As this research contributes critical insights into the multifaceted challenges associated with PATH-Fit implementation, it emphasizes the necessity for strategic interventions to enhance the effectiveness of the new tertiary physical education curriculum in the Philippines.